CAR-T therapy-based innovations in the enhancement of contemporary anti-tumor therapies - Zhang, Wan-Ying; Yang, Lang-Yu; Fan, Xing-Xing (Frontiers in Immunology, 2025)
Chimeric antigen receptor T (CAR-T) cell therapy has revolutionized the treatment landscape for hematologic malignancies; however, its efficacy in solid tumors remains limited due to antigen heterogeneity, a suppressive tumor microenvironment, and tumor-intrinsic resistance mechanisms. In parallel, immune checkpoint blockade (ICB) therapies have achieved clinical milestones but often fail due to impaired antigen presentation, interferon signaling dysregulation, and immune exclusion. Recent advances in CAR-T therapy-based technologies including multi-specific and armored CAR constructs, gene-editing strategies, and synthetic circuits offer new opportunities to overcome these barriers and expand therapeutic efficacy. Artificial intelligence (AI) has further accelerated the discovery of novel tumor antigens, optimized CAR design, and enabled real-time modeling of treatment responses. Integration of CAR-T therapy with AI-driven platforms, metabolic reprogramming, bispecific antibodies, and advanced single-cell analytics represents a powerful strategy to enhance tumor targeting and durability of response. This review summarizes emerging CAR-T therapy-based innovations, explores their synergistic applications with immunotherapies, and discusses current challenges related to safety, manufacturing, cost, and biomarker validation. These multidisciplinary efforts collectively pave the way toward more effective and personalized cancer treatment.